Street As Public Space – Reinvigorating The Linkage Of Urban Public Space at Section 14, Shah Alam Selangor - Masri, Muhammad Zaidie (2018)
Today in 2018, Shah Alam city is a fast-paced city center and helps the state to generate the economy. This rapid urban development should be in line with the wishes of the local people and governments who want to see the rapid development of the local people. Therefore, based on planning from the federal government, Shah Alam will continue to drive its economy towards the better with the development of the Light Rail Transit 3 which will be through the city of Shah Alam. This development will have a big impact on the city of Shah Alam and its residents, the public transport network is more efficient and widespread. The Light Rail Transit 3 will pass through Section 14 at Persiaran Dato Menteri. As such, the development of Section 14 should be ready to receive a point of progress in urban development. Based on the study, various weaknesses found in the city of Section 14 should be taken seriously in the future. Among the weaknesses identified is the lack of safe and comfortable pedestrian network for users. This is because the development of Light Rail Transit 3 will definitely increase the number of users and tourists who want to come to Section 14. Lastly, apart from the new development of Light Rail Transit will bring more excitement to the visitor in efficiency of public transport, walking, shopping, recreational and also to the local community about economic aspects that to help to boost economic growth.